Statistical optimisation and kinetic studies of molybdenum reduction using a psychrotolerant marine bacteria isolated from Antarctica - Darham, Syazani; Mohd Zahri, Khadijah Nabilah; Zulkharnain, Azham; Sabri, Suriana; Gomez-Fuentes, Claudio; Convey, Peter; Abdul Khalil, Khalilah; Ahmad, Siti Aqlima (MDPI AG, 2021)
The extensive industrial use of the heavy metal molybdenum (Mo) has led to an emerging global pollution with its traces that can even be found in Antarctica. In response, a reduction process that transforms hexamolybdate (Mo6+) to a less toxic compound, Mo-blue, using microorganisms provides a sustainable remediation approach. The aim of this study was to investigate the reduction of Mo by a psychrotolerant Antarctic marine bacterium, Marinomonas sp. strain AQ5-A9. Mo reduction was optimised using One-Factor-At-a-Time (OFAT) and Response Surface Methodology (RSM). Subsequently, Mo reduction kinetics were further studied. OFAT results showed that maximum Mo reduction occurred in culture media conditions of pH 6.0 and 50 ppt salinity at 15 °C, with initial sucrose, nitrogen and molybdate concentrations of 2.0%, 3.0 g/L and 10 mM, respectively. Further optimization using RSM identified improved optimum conditions of pH 6.0 and 47 ppt salinity at 16 °C, with initial sucrose, nitrogen and molybdate concentrations of 1.8%, 2.25 g/L and 16 mM, respectively. Investigation of the kinetics of Mo reduction revealed Aiba as the best-fitting model. The calculated Aiba coefficient of maximum Mo reduction rate (µmax) was 0.067 h−1. The data obtained support the potential use of marine bacteria in the bioremediation of Mo.